2019
DOI: 10.7150/thno.34813
|View full text |Cite
|
Sign up to set email alerts
|

Chronic myelogenous leukemia cells remodel the bone marrow niche via exosome-mediated transfer of miR-320

Abstract: Rationale: Reciprocal interactions between leukemic cells and bone marrow mesenchymal stromal cells (BMMSC) remodel the normal niche into a malignant niche, leading to leukemia progression. Exosomes have emerged as an essential mediator of cell-cell communication. Whether leukemic exosomes involved in bone marrow niche remodeling remains unknown.Methods: We investigated the role of leukemic exosomes in molecular and functional changes of BMMSC in vitro and in vivo. RNA sequencing and bioinformatics were employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 45 publications
4
50
0
Order By: Relevance
“…RBPs such as hnRNPA1 and hnRNPA2B1 have been shown to be involved in exosomal miRNA or lncRNA export by binding specific motifs. [43] In this study, we also observed that SFRS1, an RBP, specifically interacted with a particular sequence (GAAGAAC) in miR-22 to mediate its exosomal sorting. Additional functional factors present in exosomes may also contribute to the exosomal sorting of miR-22.…”
Section: Wwwadvancedsciencecomsupporting
confidence: 62%
“…RBPs such as hnRNPA1 and hnRNPA2B1 have been shown to be involved in exosomal miRNA or lncRNA export by binding specific motifs. [43] In this study, we also observed that SFRS1, an RBP, specifically interacted with a particular sequence (GAAGAAC) in miR-22 to mediate its exosomal sorting. Additional functional factors present in exosomes may also contribute to the exosomal sorting of miR-22.…”
Section: Wwwadvancedsciencecomsupporting
confidence: 62%
“…Exosomes are naturally released from living cells and have been well recognized to play critical roles in mediating cell-to-cell communication [132]. It is worth mentioning that the current studies about the exosomal transfer of miR-320 mainly focus on cancers [133][134][135]. For example, Stevic et al determined the miRNA profiles in exosomes from plasma of 106 epithelial ovarian cancer patients, 8 ovarian cystadenoma patients, and 29 healthy women, and they found that miR-320 was significantly enriched in the exosomes from plasma of epithelial ovarian cancer patients as compared to those of healthy women [133].…”
Section: The Effects Of Mir-320 On Glucose and Lipid Metabolism In Camentioning
confidence: 99%
“…Exosomes, which are small membrane vesicles of 30-200 nm in diameter, are secreted by different types of cells and are emerging as a novel mediator of intercellular communication and drug delivery vehicles 1, 2. As naturally derived nanovesicles, exosomes efficiently deliver exogenous RNAs (siRNAs and miRNAs) to target tissues/cells in vivo 3.…”
Section: Introductionmentioning
confidence: 99%